Persepsi pelajar Melayu terhadap sifat dan konsep malu orang Melayu - Mohd Kiram, Norazlina; Mustapha, Nik Farhan (Persatuan Linguistik Malaysia, 2013)
Shyness is one of the valued characteristics that exists in every person. For the Malays, this characteristic is not only confined to emotions, but it also holds wider meanings which form a concept. This concept encompasses the principles, behaviours, beliefs, and rules that should be observed by the Malay community. A study by Norazlina Hj. Mohd. Kiram (2010) shows that the concept of shyness which is based on the Holy Quran and Hadith can be used as a fundamental principle of life and to show the true value of a Malay. This article aims to obtain the perceptions of 172 Bachelor of Arts Malay students in the Faculty of Modern Languages and Communication at Universiti Putra Malaysia. The findings show that these Malay students understand the characteristics and concept of shyness but at a superficial level. Hence, this study is significant as it can be used as a guideline and reference for readers to gauge the extent of understanding of this unique concept among Malay students.